Ujaran kebencian di youtube, studi kasus pada kasus pembunuhan irjen pol Ferdi Sambo - siti alfiyanti fiya (Signifiѐ, 2023)
ABSTRACTYoutube is a website that contains videos about the lives of artists, celebrities and even amateur videos. This website enables its users to watch, upload and share videos publicly. Apart from being just entertainment, the videos that are uploaded also vary widely, ranging from education, tutorials, education and even cases that are still hot. On social media YouTube is equipped with a comment feature, the public can freely comment on every video uploaded by the account owner. The remarks given by netizens can be in the form of positive utterances or negative ones whose purpose is to ridicule and bring down. This cannot be avoided because the realm of social media is so broad and free. Like the murder case that occurred some time ago which was carried out by a police officer with the rank of Inspector General of Police named Ferdi Sambo, the videos shown on several YouTube accounts are filled with netizen comments, not least of which are hate speech against Ferdi Sambo. In videos uploaded by several YouTube accounts, they always receive responses from netizens whose comments globally are about hate speech in the form of, 1) provocation 2) inciting 3) insults, and even 4) defamation.